TANGGAPAN MAHASISWA UNIVERSITAS PENDIDIKAN INDONESIA TERHADAP ISU YANG BERSIFAT SARA DI ERA GLOBALISASI - Salman Alfarisi; Melza Zahra Permata; Muhammad Royyan; Callula Syifa Gantari; Supriyono (Journal of Social and Economics Research, 2023)
This research contains how the responses of the students of Universitas Pendidikan Indonesia about the issues of SARA conflicts that are developing in the current era of globalisation. The purpose of this research is to find out the level of awareness of students on the issues of racial conflicts that are developing in the current era and how their attitudes in overcoming this. The informants in this study are students from various batches, study programmes and faculties. This research uses a quantitative descriptive method in which this research only describes the content of a variable in the study, not intended to test certain hypotheses. These data were collected through questionnaires distributed to students of Universitas Pendidikan Indonesia. Overall, the average result is 82.73% which is included in the high category which means it shows that students of Universitas Pendidikan Indonesia respond to SARA issues in the era of globalisation with high. Although the level of awareness of students is high on the issues of SARA conflict, we must remain vigilant and selective in choosing and sorting out the information we get through social media.